MORPHOLOGICAL BASES OF STRUCTURAL ORGANIZATION OF RED BONE MARROW FOR EXPERIMENTAL STUDIES - Nebesna, Z.M. (World of Medicine and Biology, 2017)
It is known from the literature that some hematological diseases are associated with a violation of metabolic processes in the cell, leading to abnormalities in the functioning of the red bone marrow, but the cause of such a shift in metabolic processes is unknown. Recently, in the pathogenesis of oncological diseases increasing importance is given to the morphological structures involved in the local regulation of tissue processes, as well as biologically active substances that are produced by them. Therefore, the study of hematopoiesis in the red bone marrow is necessary in order to carry out an analysis in the mechanisms that regulate the processes of growth and differentiation of cells in the normal state and pathology, which will enable to find the vector of influence for the correction of the morbid condition.